Dengue Fever in Turkey: Cases and Public Health Implications - Tugba Sari; Dilek Menemenlioglu; Perihan Alkan; Ebru Aydin; Hasan Irmak; Irfan Sencan (Acta Clinica Croatica, 2024)
Dengue virus is endemic in almost all tropical and sub-tropical countries which also are popular tourist destinations, and it is a major international public health problem. Presented herein are six travel-associated dengue fever cases diagnosed between 2016 and 2017 in Turkey. The current situation in Turkey and in the world, as well as epidemiological data regarding the vector and relationship between the disease and traveling are also discussed. This retrospective study evaluated dengue fever cases identified using serological and molecular methods between January 2016 and February 2017 in the National Virology Reference Laboratory. Two patients had a travel history to Maldives, two patients to Thailand, one patient to Sri Lanka, and one patient to Guiana. Fever was present in all cases. The most common other symptoms were fatigue, myalgia, and arthralgia. Increased liver enzymes (50%) and thrombocytopenia (66%) were the most commonly encountered laboratory changes. In conclusion, imported dengue fever cases are increasingly reported due to facilitation of international travels and increasing commercial activities. Before traveling to a region where dengue fever is endemic, consulting a travel medicine counseling desk or a doctor is suggested. Dengue fever should be kept in mind in a patient with travel history presenting with fever, elevated liver enzyme and thrombocytopenia.